#BeSeen: understanding young people’s views of the motivation and impacts of sharing self-harm imagery online and use of their social media data for research—a UK participatory arts-led qualitative study - Ann John; Ashrafunnesa Khanom; Todd Smith; Amanda Marchant; Dana Dekel; Harley Morgan; Sarah Tombs; Karen Ingham (BMJ Open)
Objectives This study explored the views of young people from diverse backgrounds, with or without a history of self-harm, on the motivation and impacts of sharing self-harm imagery online and the use of their social media data for mental health research.Design Thematic analysis of 27 semi-structured one-to-one interviews.Setting Two workshops were conducted in 2021.Participants We recruited 27 study participants aged 16–24 (60% male). Sixteen (59%) participants were refugee and asylum seekers (RAS).Results Two main themes were generated: (1) Online imagery of self-harm captured perceived motivations for sharing such images, the potential impacts on others and possible need of censorship. This theme was characterised by mixed attitudes towards motivations for sharing, with some perceiving this as attention seeking, while others thought of it as help seeking or sharing of pain. Overall, participants agreed that images of self-harm can be triggering and should include trigger warnings. (2) Data sharing for mental health and self-harm research captured views on the use of social media posts and images for research purposes, and levels of trust in public and private organisations. It outlined positive views on their data being shared for research for public benefit, but highlighted issues of consent. The two most trusted organisations to hold and conduct research were the National Health Service and Universities. Participants from the RAS group were more inclined to agree to their data being used and had higher levels of trust in government.Conclusion Young people care about their privacy and use of their data even when it is publicly available. Coproduction with young people of resources to support understanding and develop innovative solutions to gaining informed consent for data sharing and research for public benefit is required. Young people from excluded communities, post-immigration RAS and males should be purposively involved in future social media research.